Micronutrients, antioxidant activity, and tocochromanol contents of selected pigmented upland rice genotypes - Ahmad, Faiz; Musa, Mohamed Hanafi; Md. Abdul Hakim,; Yusop, Mohd Rafii; Abdullah, Siti Nor Akmar (Friends Science Publishers, 2015)
Pigmented rice genotypes have high nutritive value compared to white rice genotypes. These genotypes contain high levels of micronutrients and antioxidant compounds, such as polyphenols, tocochromanols and oryzanol. In this experiment, 42 pigmented rice genotypes obtained from the International Rice Research Institute (IRRI) were evaluated to determine micronutrient content, antioxidant activity and vitamin E content. The results revealed that the micronutrient content, antioxidant activity and tocochromanol content of all genotypes varied. Iron (Fe) was the most abundant micronutrient followed by Zn, Mn and Cu. The antioxidant DPPH scavenging effect among all genotypes ranged from 31.85 to 98.45%. The tocotrienol content was higher than tocopherol in grains of selected pigmented rice genotypes. Among rest of genotypes, IR3257-13-56, IR5533-14-1-1 and Khao gam (niaw) contained high micronutrient content and antioxidant properties compared to others. These genotypes could also be potentially used further for breeding program to improve the rice plant with high micronutrient content and antioxidant properties.